In Silico Comparative Evaluation of Biotechnology-Based Engineered Bacterial Therapeutic Platforms for Targeted Sensing, Controlled Payload Delivery, and Biocontainment : Evaluasi Komparatif In Silico terhadap Platform Terapi Bakteri Rekayasa Berbasis Bioteknologi untuk Deteksi Bertarget, Pengiriman Muatan Terkendali, dan Pengendalian Biologis - Raghda Saad Jameel (Indonesian Journal on Health Science and Medicine, 2026)
General Background Engineered bacterial therapeutics have emerged as programmable living systems capable of site-specific sensing and controlled therapeutic delivery. Specific Background Despite rapid advances in synthetic biology, there remains difficulty in selecting optimal platform architectures due to the lack of structured comparative evaluation tools. Knowledge Gap Existing literature lacks a decision-oriented framework that systematically compares engineered bacterial therapeutic platforms across integrated engineering and translational criteria. Aims This study aims to develop an in silico comparative evaluation model to assess representative therapeutic platforms based on specificity, payload control, biosafety, manufacturability, and translational readiness. Results The analysis identifies dual-input logic-gated biocontainment-enabled systems as the highest-ranked platform, followed by biomarker-responsive circuits, while constitutive and tumor-colonizing systems show lower balanced performance. Novelty The study introduces a weighted multi-criteria scoring framework that transforms descriptive knowledge into a structured decision-making tool for platform selection. Implications The proposed model provides a systematic basis for guiding design prioritization, optimization strategies, and future experimental validation in engineered bacterial therapeutics. Keywords: Engineered Bacterial Therapeutics, Synthetic Biology, In Silico Evaluation, Gene Circuits, Biocontainment Key Findings Highlights Dual-input architectures achieve highest balance across evaluation criteria Biomarker-responsive systems provide strong contextual activation with moderate complexity Simpler and tumor-targeting designs show limitations in safety and control balance